Advanced characterization of natural biofilm on nanofiber scaffold - Svobodová, Lucie; Lederer, Tomáš; Rosická, Petra; Svoboda, Přemysl; Novák, Libor; Dostálková, Alžběta; Jirků, Vladimír (Physiological research, 2019)
Nanofiber scaffolds provide numerous advantages over common carriers engineered for microorganisms. The most important advantage is an increased speed of primary surface colonization (up to four times faster), which shortens the time required for the areal biofilm formation and optimum performance of attached microorganisms (higher efficiency of biological activity of up to twice as fast). Image analysis predicts early formation of biofilm even in beginning stages; analysis of biofilm reveals the different structures of bacterial colonies on both scaffolds (higher porosity, size, and number of bacterial colonies on nanofiber's surface). The image analysis correlates well with determinations of dry matter (linear correlation of 0.96) and proteins (linear correlation of 0.89).
Keywords: Biofilms; Polyurethanes; nanovlákna; Porosity; poréznost; kultivační média; biofilmy; Culture Media; polyurethany; Rhodococcus; Nanofibers